2001
DOI: 10.3168/jds.s0022-0302(01)74570-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sustained Release Bovine Somatotropin(Sometribove) on Animal Health in Commercial Dairy Herds

Abstract: The health of dairy cows given bovine somatotropin (bST) for one lactation was evaluated in 28 commercial herds located in four regions of the United States. At least six herds were in a region and at least one herd/region contained fewer than 60 cows. Cows (n = 1213) were assigned randomly to control or bST groups and were treated beginning in wk 9 to 10 of lactation and every 14 d until dry-off or d 400 of lactation. Management was according to site practices. Cows were observed for health-related signs by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
3
27
2
5
Order By: Relevance
“…The increases in daily milk production from 3 to 5 L/day in response to rBST application were also observed in studies by several authors (Hartnell et al, 1991;LuccI et al, 1998;Collier et al, 2001;Carriquiry et al, 2008). For variable total milk increment, animals producing less than 20 L/day showed no significant difference in the milk production response in relation to decreased rBST application interval from 14 to 10 days; for rBST application interval of 12 days, significant difference compared to other intervals was observed, with production response of 115.54 L compared to 166.60 and 154.52 L for rBST application interval of 14 and 10 days, respectively.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The increases in daily milk production from 3 to 5 L/day in response to rBST application were also observed in studies by several authors (Hartnell et al, 1991;LuccI et al, 1998;Collier et al, 2001;Carriquiry et al, 2008). For variable total milk increment, animals producing less than 20 L/day showed no significant difference in the milk production response in relation to decreased rBST application interval from 14 to 10 days; for rBST application interval of 12 days, significant difference compared to other intervals was observed, with production response of 115.54 L compared to 166.60 and 154.52 L for rBST application interval of 14 and 10 days, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…Studies have shown that treatment with an extended-release formulation containing 500 mg rBST at intervals of 14 days can increase milk production from 3 to 5 kg/day, on average (Collier et al, 2001). The mechanism of action of somatotropin on the mammary gland occurs indirectly by increase factor concentration of the insulin-like growth (IGF-1), compound that plays a fundamental role in the control of metabolism and physiological processes in cattle (Gulay and Hatipoglu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The EU Committee on Veterinary Medical Products (CVMP) concluded that there was no evidence of an effect of r-bST supplementation on the incidence of mastitis. This is supported by many other studies Collier et al, 2001). The incidence of mastitis is linked to the level of milk production.…”
Section: Effects Of R-bst On Animal Healthsupporting
confidence: 77%
“…This difference represents an increase in the total milk yield of 5.3% per cow. Although this result is within the range of increase expected in response to the bST-r in this region where heat stress is high, it is lower than those reported by other authors: Cervantes and Vejar (1997) reported 8.3% of increase when they injected the bST-r to Holstein cows in intermediate stages of lactation under severe heat stress; while Collier et al (2001) found an increase of 9.1% and Stehr et al (2001) observed 27% of increase. However, it should be considered that the percentage of increase estimated in the present work was made on the same cow injected with bST-r; whereas in the studies carried out by the other investigators, the increase was estimated by comparing the milk yield obtained in control animals with those of animals treated with bST-r.…”
Section: Resultscontrasting
confidence: 51%